2006
DOI: 10.1074/jbc.m510944200
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of Santonin into a Diacetoxy Acetal Form Confers the Ability to Induce Differentiation of Human Promyelocytic Leukemia Cells via the Down-regulation of NF-κB DNA Binding Activity

Abstract: Many sesquiterpene lactone compounds either induce or enhance the cell differentiation of human leukemia cells. However, we reported in a previous study that santonin, a eudesmanolide sesquiterpene lactone, exerts no effects on the differentiation of leukemia cells. In this report, to evaluate the possibility of chemically modifying santonin into its derivatives with differentiation inducing activity, we synthesized a series of santonin derivatives, and determined their effects on cellular differentiation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
9
0
2
Order By: Relevance
“…O atraso da germinação faz com que as plântulas demorem mais para emergir, tornando-se propensas ao ataque de predadores, pragas e patógenos e ainda, este atraso pode resultar em uma competição intra e interespecífica por recursos do meio devido aos diferentes tamanhos das plantas existentes no mesmo ambiente (KAPPES et al, 2010 Uma hipótese que pode ser responsável por este efeito inibitório do extrato de folhas de cártamo sobre as raízes de canola, provavelmente, seja a presença de lactonas sesquiterpênicas, que, segundo Kim et al (2006), é um dos principais metabólitos secundários da família Asteraceae, encontrado em diversas plantas dentre elas o girassol (Helianthus annuus L.) e o crisântemo (Chrysanthemum cinerariaefolium L.). Este composto pode ser depositado diretamente no solo pela água da chuva ou gradualmente liberado durante a decomposição das folhas, afetando o crescimento de plantas vizinhas (FRITZ et al, 2007).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…O atraso da germinação faz com que as plântulas demorem mais para emergir, tornando-se propensas ao ataque de predadores, pragas e patógenos e ainda, este atraso pode resultar em uma competição intra e interespecífica por recursos do meio devido aos diferentes tamanhos das plantas existentes no mesmo ambiente (KAPPES et al, 2010 Uma hipótese que pode ser responsável por este efeito inibitório do extrato de folhas de cártamo sobre as raízes de canola, provavelmente, seja a presença de lactonas sesquiterpênicas, que, segundo Kim et al (2006), é um dos principais metabólitos secundários da família Asteraceae, encontrado em diversas plantas dentre elas o girassol (Helianthus annuus L.) e o crisântemo (Chrysanthemum cinerariaefolium L.). Este composto pode ser depositado diretamente no solo pela água da chuva ou gradualmente liberado durante a decomposição das folhas, afetando o crescimento de plantas vizinhas (FRITZ et al, 2007).…”
Section: Resultsunclassified
“…Dentre as espécies desta família, existem várias plantas de uso medicinal e utilizadas na agricultura que possuem compostos alelopáticos já identificados (BORGO et al, 2010;GASPARRETTO et al, 2010). Na cultura do girassol são encontrados terpenos e compostos fenólicos (KUPIDLOWSKA et al, 2006 Os metabólitos secundários dessa família, por possuírem interesse médico e farmacológico, são objetos de estudo de muitas pesquisas (VERDI et al, 2005).…”
Section: Introductionunclassified
“…Previously we have reported that sesquiterpene lactone compounds were demonstrated to induce leukemia cell differentiation (Kim et al 2002(Kim et al , 2005. Additionally, sesquiterpene lactones compounds such as santonin could be chemically modified into their derivatives, which strongly enhanced collaborative effects on leukemic cell differentiation (Kim et al 2006(Kim et al , 2008. Although arsantin used in this study is a sesquiterpene lactone compound which is known to be present in Artemisia santolina, its biological effects on leukemia cell differentiation have not been reported.…”
Section: Introductionmentioning
confidence: 85%
“…1), the acetal analogue of α-santonin that contains a non-lactone ring, had remarkable anti-leukemic activities, inducing HL-60 cell differentiation via down-regulation of NF-κB binding activity (Kim et al, 2006a). Also, we have investigated the SAR of DAAS derivatives (Kim et al, 2006b;Kim et al, 2008a).…”
Section: Introductionmentioning
confidence: 99%